2006
DOI: 10.1038/modpathol.3800574
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-β is expressed in stromal cells of fibroadenoma and phyllodes tumors of the breast

Abstract: An estrogen dependency has been suggested for the growth of fibroadenomas: however, thus far, none of the steroid hormone receptors acting on breast tissues has been demonstrated in the stroma of breast fibroepithelial lesions. In this study, the expression of estrogen receptor (ER)-a and -b was investigated by immunohistochemistry in 33 fibroadenomas and in 30 benign, three borderline and seven malignant phyllodes tumors, all with spindle cell growth and in one distant metastasis. In addition, the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 31 publications
2
50
0
2
Order By: Relevance
“…A study reported that ERα was mainly expressed by epithelia cells while no expression in the stromal cells [15] compared to the present study, only 7.1% ERα expression in malignant PT and absent in borderline and benign PT. Previous studies demonstrated that ERb was found in stromal cells in the FA and PT.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…A study reported that ERα was mainly expressed by epithelia cells while no expression in the stromal cells [15] compared to the present study, only 7.1% ERα expression in malignant PT and absent in borderline and benign PT. Previous studies demonstrated that ERb was found in stromal cells in the FA and PT.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies demonstrated that ERb was found in stromal cells in the FA and PT. [13,15] We opine that ERb showed better expression than ERα which was highly detectable in the stromal component. The greater expression of ERb suggests that it may be the main ER in the breast.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, for ER/PR scoring, we are only interested in the staining that occurs to tumour nuclei. On occasion the IHC stain binds to non-tumour nuclei, [13][14][15] but this has no relevance to the score and should be ignored. Therefore, to ensure that only the correct parts of the tissue are being scored, the tumour nuclei must be isolated from the remaining tissue.…”
Section: Automatic Er/pr Scoringmentioning
confidence: 99%